Cooperative membership, contracts, and production efficiency: A selectivity-corrected analysis of smallholder farmers - Khanal, Aditya R.; Mishra, Ashok K.; Kumar, Anjani (Agricultural and Applied Economics Association, 2019)
Background: Cooperatives are considered as efficient institutional innovation for smallholders to access input and output; Cooperatives can help balance the power between contractors and smallholders in contract farming (CF); Cooperatives play an integral role in CF in Nepal (Mishra et al. 2018); The relationship between participation in agricultural cooperatives and farm performance is not fully conclusive; some studies have explored the production efficiency about cooperative membership (Abate et al. 2014; Gedara et al. 2012) and have found mixed evidence about the relationship; None of the previous studies have examined the relationships between cooperative membership and technical efficiency for the high-value crops, like tomato in a developing country context; This study estimates the selectivity-corrected stochastic frontier analysis for the tomato growers in Nepal, accounting for selection bias in efficiency estimation, emphasizing the role of cooperative CF on technical efficiency.